Could assortment rationalisation help reduce dood waste in grocery stores? - Elvira Saez-Gonzalez; Juan Carlos Gázquez-Abad (Amfiteatru Economic, 2024)
Nowadays, sustainable development and waste management are the topics on which academia is focusing. The size of the retail assortment plays a crucial role in influencing the levels of food waste in grocery stores. Additionally, the analysis of retail food waste highlights that the planning of assortment sizes is essential for reducing waste, particularly in products with expiration or best-before dates, such as fresh fruit and vegetables, where a few products contribute significantly to overall waste. This work aims to explore assortment rationalisation as a way to prevent food waste from perishable products in retail grocery stores and, therefore, improve the sustainability generated by food retail chains in developed countries. Although many articles analyse the relationship between retail store operations and food waste prevention, to our knowledge, there is little research that explicitly focuses on assortment. From the review of the specialised literature, few studies have been detected on the effects of the grocery store assortment on food waste. This paper attempts to fill part of this research gap, by focusing on establishing a link between assortment rationalisation and food waste in grocery retail stores through a review of the scientific literature on proactive food waste prevention strategies, presenting an opportunity for future research in this emerging research area, and providing practical advice to retail chains concerned about sustainability. In conclusion, this study serves as an initial approach to this topic and is a useful starting point for future research in this area. Our primary contribution lies in highlighting a certain scarcity of studies on the retailer's assortment as a proactive food waste prevention strategy.
Keywords: M14; M21; M31; 330; assortment rationalisation; assortment reduction; assortment size; retail food waste; retail food waste prevention strategies; grocery stores; sustainability